2008
DOI: 10.1108/09526860810841183
|View full text |Cite
|
Sign up to set email alerts
|

The influence of service quality and patients' emotions on satisfaction

Abstract: The research shows empirical evidence about the effect of both patient's emotions and service quality on satisfaction with healthcare services. Findings also provide a model that includes valid and reliable measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 50 publications
(61 reference statements)
1
49
0
Order By: Relevance
“…We have developed a new instrument, the Quality of Prenatal Care Questionnaire (QPCQ), through a rigorous process of item generation and psychometric testing. The QPCQ was designed to be completed by women who received prenatal care, consistent with growing acknowledgement of the value of the consumer’s viewpoint in evaluating quality of health care [22,23,62,63]. The final 46-item version of the QPCQ demonstrated construct validity, as well as acceptable internal consistency and test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have developed a new instrument, the Quality of Prenatal Care Questionnaire (QPCQ), through a rigorous process of item generation and psychometric testing. The QPCQ was designed to be completed by women who received prenatal care, consistent with growing acknowledgement of the value of the consumer’s viewpoint in evaluating quality of health care [22,23,62,63]. The final 46-item version of the QPCQ demonstrated construct validity, as well as acceptable internal consistency and test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Research to empirically test the relationships between these variables provides evidence that perceived quality affects satisfaction with health care, and that quality of care and consumer satisfaction are distinct constructs [23,24]. Quality is defined as a judgment or evaluation of several dimensions specific to the service being delivered, whereas satisfaction is an affective or emotional response to a specific consumer experience [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are in no position to assess the technical quality of the process of care [24,25], and their judgment is primarily based on the interpersonal aspect of care that they receive and the manner in which medical care is delivered. For instance, the doctors’ technical skill scale is not specifically related to the quality of the surgical act and rather reflects the patient perception of the doctors’ knowledge and experience of his illness, the quality of global treatment he provided and the attention paid to the patients’ physical problem.…”
Section: Discussionmentioning
confidence: 99%
“…function of hospitals and found that those who perceived a better customer service delivery, in 2 terms of factors such as courtesy, promptness, and cleanliness, indicated significantly higher 3 satisfaction levels. Similarly, Vinagre and Neves (2008) found that patients' evaluations of a 4 hospital's service quality had a significant impact on their satisfaction with their doctors, nurses, 5 and the hospital's overall service performance. Thus, while supported by studies in the EBD 6 literature, our inclusion of both the product and service dimensions of hospitality in healthcare is 7 also consistent with Bitner's (1992Bitner's ( , 1990 We identified three types of patient responses relevant to testing the application of 20 hospitality elements in healthcare: preferences, perceptions, and behavioral consequences.…”
Section: Environmental Stimuli: Product and Service Dimensions Of Hosmentioning
confidence: 99%